2011
DOI: 10.1002/ppul.21454
|View full text |Cite
|
Sign up to set email alerts
|

Effect of night symptoms and disease severity on subjective sleep quality in children with non‐cystic‐fibrosis bronchiectasis

Abstract: Patients with bronchiectasis have disturbed sleep associated with severity of disease. Night symptoms increase the risk of poor sleep quality. Sleep disordered breathing and sleep quality should be assessed in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 47 publications
0
26
0
Order By: Relevance
“…This is, to our knowledge, the first study to investigate the prevalence of sleep disturbances and daytime sleepiness, and their relationship with QoL in adults with bronchiectasis by utilizing standardized questionnaires [9]. Although daytime sleepiness did not differ considerably from healthy subjects, the prevalence of sleep disturbances was an approximately 2-fold higher in bronchiectasis patients.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This is, to our knowledge, the first study to investigate the prevalence of sleep disturbances and daytime sleepiness, and their relationship with QoL in adults with bronchiectasis by utilizing standardized questionnaires [9]. Although daytime sleepiness did not differ considerably from healthy subjects, the prevalence of sleep disturbances was an approximately 2-fold higher in bronchiectasis patients.…”
Section: Discussionmentioning
confidence: 79%
“…To date, the literature on this topic in bronchiectasis has been limited. A recent study [9] reported that children with bronchiectasis had a high prevalence of sleep disturbances associated with nocturnal respiratory symptoms and disease severity. However, apart from focusing on children, the sample size in their study was insufficient to warrant a conclusive finding, and the potential impact of psychological status on sleep disturbances was also unclear.…”
Section: Introductionmentioning
confidence: 99%
“…There are several reported causes of disruption of sleep architecture in CF, including hypoxemia, cough, obstructive apneas, and pain [30,32,33]. Less is known about the impact of non-CF bronchiectasis, but one study of 54 children reported that poor sleep quality, frequent nocturnal respiratory symptoms, and obstructive sleep apnea were common [34].…”
Section: Cystic Fibrosismentioning
confidence: 99%
“…Although BE is commonly due to cystic fibrosis (CF) in developed countries, non-CF etiologies are also common in developing countries [1,2,3]. …”
Section: Introductionmentioning
confidence: 99%